Game-Based Learning Model of Pencak Silat for Early Childhood to Build Self-Efficacy - Lulut Gilang Saputra; Lokananta Teguh Hari Wiguna; Arief Darmawan; Muhammad Ilham Vahrudin; Muhammad Akbar Cendra Wirayudha (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2025)
This study aims to develop a pencak silat training model for early childhood that is suitable as a pencak silat textbook for kindergarten students at Aisyiyah Bustanul Athfal 9 Malang. Research and Development (R&D) was the research method used in this study. The data collection instruments used by the researcher included interviews, observations, questionnaires, and documentation, with the results being qualitative and quantitative data. The product validation process involved several experts, including early childhood learning experts, pencak silat material experts, and media experts. Then, the product underwent a trial process in small and large groups. The results of the product validation obtained a percentage of 82% from early childhood learning experts, 87% from pencak silat material experts, and 90% from media experts, so it was considered very valid and meaningful to be used. The small group trial results obtained a percentage of 82%, and the large group trial results obtained a percentage of 84%, making it highly valid and meaningful for implementation. Thus, the pencak silat game-based learning model for students at Aisyiyah Bustanul Athfal 9 Malang Kindergarten shows that the game-based pencak silat book for kindergarten-aged children is highly valid and suitable for use.